2015
DOI: 10.3390/su71013713
|View full text |Cite
|
Sign up to set email alerts
|

A Field Experiment on Enhancement of Crop Yield by Rice Straw and Corn Stalk-Derived Biochar in Northern China

Abstract: Biochar, a green way to deal with burning and burying biomass, has attracted more attention in recent years. To fill the gap of the effects of different biochar on crop yield in Northern China, the first field experiment was conducted in farmland located in Hebei Province. Biochars derived from two kinds of feedstocks (rice straw and corn stalk) were added into an Inceptisols area with different dosages (1 ton/ha, 2 ton/ha or 4 ton/ha) in April 2014. The crop yields were collected for corn, peanut, and sweet p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 36 publications
4
21
1
Order By: Relevance
“…Incorporation of biochar steadily neutralized the soil pH value, and increased Mg and P availability in B-and BB-amended soils and Ca in BB-amended soil. These results are in line with those of previous reports (Yang et al, 2015), confirming the rate-dependent modifications of pH. Increases in exchangeable Ca and available P reflect the high base cations and P concentration of the biochar.…”
Section: Main Soil Propertiessupporting
confidence: 93%
“…Incorporation of biochar steadily neutralized the soil pH value, and increased Mg and P availability in B-and BB-amended soils and Ca in BB-amended soil. These results are in line with those of previous reports (Yang et al, 2015), confirming the rate-dependent modifications of pH. Increases in exchangeable Ca and available P reflect the high base cations and P concentration of the biochar.…”
Section: Main Soil Propertiessupporting
confidence: 93%
“…. Yang et al (2015) mentioned that biochar amendment could enhance yields, and biochar from rice straw showed a more positive effect on the yield of corn, peanut, and winter wheat than corn stalk biochar. Islami et al (2011) found that increases in maize yield following biochar application.…”
Section: Figmentioning
confidence: 99%
“…Consequently, the low rate of 10 Mg ha −1 (~0.5 mass% assuming thorough incorporation in the top 15 cm soil layer) has been the most common select in field biochar applications [67]. Depending on the biochar source and the soil type, biochar amendment at as low as 0.1 mass% (2 Mg ha −1 ) may yield significant effects on plant growth [88]. Our research indicates that to secure the evident, long-term soil health improvement benefits, wood-and crop residue-derived biochars may be applied cumulatively at 2-5 mass% soil (40-100 Mg ha −1 ) and manure-derived biochars be applied at 1-3 mass% soil (20-60 Mg ha −1 ) to cropland.…”
Section: The Right Application Ratementioning
confidence: 99%